2023
DOI: 10.1038/s41467-023-38329-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic models project bird invasions with accuracy

Abstract: Invasive species pose a major threat to biodiversity and inflict massive economic costs. Effective management of bio-invasions depends on reliable predictions of areas at risk of invasion, as they allow early invader detection and rapid responses. Yet, considerable uncertainty remains as to how to predict best potential invasive distribution ranges. Using a set of mainly (sub)tropical birds introduced to Europe, we show that the true extent of the geographical area at risk of invasion can accurately be determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 163 publications
(171 reference statements)
0
3
0
Order By: Relevance
“…The same applies for the common waxbill, for which the distribution and dispersal of well-studied invasive populations in Iberia have been found to be strongly influenced by climate and habitat gradients (Sullivan & Franco, 2018), but accurate prediction of invasion risk is difficult (Stiels et al, 2015). In an attempt to improve accuracy, Strubbe et al (2023) used thermal physiological approaches to model the species’ potential European distribution range expansion, but faced challenges in inferring key functional traits because of a lack of empirical data from wild individuals, forcing them to rely on allometric predictions. Moreover, while experiments on captive birds have value, the non-natural biotic and abiotic conditions to which animals are exposed can lead to important ecophysiological changes (Beaulieu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The same applies for the common waxbill, for which the distribution and dispersal of well-studied invasive populations in Iberia have been found to be strongly influenced by climate and habitat gradients (Sullivan & Franco, 2018), but accurate prediction of invasion risk is difficult (Stiels et al, 2015). In an attempt to improve accuracy, Strubbe et al (2023) used thermal physiological approaches to model the species’ potential European distribution range expansion, but faced challenges in inferring key functional traits because of a lack of empirical data from wild individuals, forcing them to rely on allometric predictions. Moreover, while experiments on captive birds have value, the non-natural biotic and abiotic conditions to which animals are exposed can lead to important ecophysiological changes (Beaulieu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Urban areas form urban heat islands (UHIs) 40 , which are consistently warmer than their surrounding habitats 41 . The invasion risk of mainly (sub-) tropical birds in Europe has been linked to the thermal niche of a species, which is influenced by morphological traits 42 . The morphological trait of body size is a critical determinant of metabolic rate, dispersal, and other life history traits 43 , 44 .…”
Section: Introductionmentioning
confidence: 99%
“…While ecophysiological insights have so far not been applied in polyploidy research, these approaches are opening new avenues and changing our views in other ecological fields. For example, using biophysical mechanistic modelling, Strubbe et al (2023) showed that potential ranges of invasive bird species are constrained by body size and metabolic rates, forecasting a highly likely further spread of these non-native species. Using DEB models has also been proven useful for improving ecological predictions in variable environments (Monaco & McQuaid 2018), especially in ecotoxicology, where this type of models aid in transforming individual level responses and traits into population and higher-level dynamics (Jager et al 2014).…”
Section: Introductionmentioning
confidence: 99%